Comparative Analysis of Indonesia and Malaysia Budget Policies in Handling the Covid-19 Pandemic from Maqâshid al-Syarî`Ah Perspective - Purnomo, Joko Hadi; Rusgianto, Sulistya; Hidayati, Niswatin Nurul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This research aimed to analyze state spending for handling Covid-19 from the perspective of maqâshid al-syarî`ah (sharia objective). The analysis was carried out by mapping the Covid-19 budget in five dimensions of maqâshid al-syarî`ah, including hifdz al-dîn (protection of religion), hifdz al-nafs (protection of the soul), hifdz al-‘aql (protection of thinking), hifdz al-nasl (protection of offspring/family), and hifdz al-mâl ((protection of property). The mapping results were compared with the budget for each dimension of maqâshid al-syarî`ah and the total budget for Covid-19; and finally compared to the total of state budget; as well as total debt. This research used a descriptive quantitative approach. The object of research was ASEAN member countries with the criteria of having more than 50% Muslim population, and their state budget data was available on the official website of the Ministry of Finance which can be accessed via the internet. The results of the research, in Indonesia and Malaysia, allocated funds for handling Covid-19 for the fulfillment of hifdz al-nafs, hifdz al-mâl, but not for the fulfillment of hifdz al-nafs funds. In Indonesia, there was no budget allocation for hifdz al-dîn, hifdz al-‘aql, and hifdz al-nafs. Malaysia has allocated Covid-19 handling funds for hifdz al-dîn and hifdz al ‘aql. Penelitian ini bertujuan untuk menganalisis belanja negara untuk penanganan Covid-19 dari perspektif maqâshid al-syarî`ah. Analisis dilakukan dengan memetakan anggaran Covid-19 dalam lima dimensi maqâshid alsyarî`ah, antara lain hifdz al-dîn, hifdz al-nafs, hifdz al-‘aql, hifdz al-nasl, dan hifdz al-mâl. Hasil pemetaan tersebut dibandingkan dengan anggaran untuk masing-masing dimensi maqâshid al-syarî`ah dan total anggaran untuk Covid-19; dan terakhir dibandingkan dengan total APBN; serta total hutang. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Objek penelitian adalah negara-negara anggota ASEAN dengan kriteria berpenduduk muslim lebih dari 50%, dan data APBN-nya tersedia di situs resmi Kementerian Keuangan yang dapat diakses melalui internet. Hasil penelitian menunjukkan bahwa di Indonesia dan Malaysia, alokasi dana penanganan Covid-19 untuk pemenuhan hifzh al-nafs, hifzh al-mâl, namun tidak untuk pemenuhan dana hifdz al-nafs. Di Indonesia, tidak ada alokasi anggaran untuk hifdz al-dîn, hifdz al-‘aql, dan hifdz al-nafs. Malaysia telah mengalokasikan dana penanganan Covid-19 untuk hifdz al-dîn dan hifdz al-‘aql